Effects of influenza immunization on pneumonia in the elderly - Jung Yeon Heo; Joon Young Song; Ji Yun Noh; Min Joo Choi; Jin Gu Yoon; Saem Na Lee; Hee Jin Cheong; Woo Joo Kim (Taylor & Francis Group, 2018)
Influenza virus is a common pathogen implicated in respiratory tract infections, annually affecting up to 20% of the general population, and pneumonia is a leading cause of death after influenza infection. Post-influenza pneumonia is especially common in the elderly and chronically ill patients. The risk of post-influenza pneumonia is significantly increased according to the number of concurrent comorbidities. Vaccination is the primary measure used to abate influenza epidemics and associated complications. In meta-analyses, influenza vaccine significantly reduces pneumonia- and influenza-related hospitalizations, with a vaccine effectiveness of 25-53%. However, considering the poor effectiveness of conventional influenza vaccines in the elderly, several highly immunogenic influenza vaccines have been developed. Further evaluations of the comparative effectiveness of diverse vaccine formulations are warranted to assess their utility for preventing influenza infection, post-influenza pneumonia, and related hospitalization/mortality. Based on cost-effectiveness and budget impact analysis, influenza vaccination strategies should be tailored in the elderly.